Analysis of the Need for Teaching Materials for Japanese Writing Courses (Sakubun II) Based on 21st Century Skills - Cut Erra Rismorlita; Frida Philiyanti (Universitas Negeri Semarang, 2023)
This study aims to collect the information needed to find a form of teaching material that fits the needs of students and the demands of a new 21st-century skill-based curriculum in writing courses at the basic secondary level (Sakubun II). The research method used is R&D with a mixed approach. These qualitative and quantitative approaches aim to describe the needs of students, lecturers, and study programs for writing teaching materials following the 21st-century curriculum. Data collection techniques were carried out in three ways: reviewing documents, questionnaires, and observation. The results showed that the Japanese Language Education Study Program FBS UNJ needed teaching materials focused on achieving writing skills and could also motivate students to have ideas and be creative in writing easily. Regarding the structure of teaching materials, various teaching materials are needed to encourage students to write in digital literacy discourse. From the questionnaire results, three needs were found at the top level, namely the need for teaching materials that focus on critical thinking skills, creativity, and basic literacy, so the portion of activities that can accommodate these needs must be enlarged.